SLOPE REINFORCEMENT ANALYSIS WITH BORED PILE AND GROUND ANCHOR USING FINITE ELEMENT METHOD AND LIMIT EQUILIBRIUM METHOD FOR EMBANKMENT FAILURE CASE IN RIAU ISLANDS - AKBAR (NIM : 15006075); Pembimbing : Prof. Ir. Masyhur Irsyam, M.SE, Ph.D., REMON
The geotechnical problem that occured is a failure of embankment slope which happened to the gas station in Riau Islands. This slope instability problem has occurred since its construction period which started in 2002. In year 2004, a remedial action was conducted by placing a counterweight. However, the problem still occures. In 2006, reduction of soil mass by excavation was performed on the top of embankment to increase safety factor of the slope. However, based on the result of visual observation, there were some cracks at surface of soil that indicate the slope failure still occuring. This is confirmed by the results of inclinometer observation. In this final assignment, back calculation analysis is performed to ensure failure mechanism is suitable with inclinometer observation. The result of analysis used to analyze the alternative reinforcement. The method that will be used in slope stability analysis is finite element method and verified with limit equilibrium method. Whereas, the slope reinforcements that were analyzed consist of bored pile reinforcement and ground anchor reinforcement. The analyses showed that the slope reinforcement using bored pile or ground anchor could increase safety factor > 1.25.